Correlates of Intimate Partner Homicide among Male Suicide Decedents with Known Intimate Partner Problems. Issue 6 (12th June 2019) - Logan, Joseph E.; Ertl, Allison; Bossarte, Robert
Abstract : Objective: Intimate partner (IP) problems are risk factors for suicide among men. However, there is little understanding of why some male suicide decedents who had such problems killed their partners before death (i.e., "IP homicide‐suicide"), while most of these decedents did not. To inform prevention efforts, this study identified correlates of IP homicide among male suicide decedents with known IP problems. Methods: We examined IP homicide correlates among male suicide decedents aged 18+ years who had known IP problems using 2003–2015 National Violent Death Reporting System data. Prevalence odds ratios and 95% confidence intervals were estimated for demographic, incident, and circumstance variables. IP homicide‐suicide narratives were examined to identify additional prevention opportunities. Results: An estimated 1, 504 (5.0%) of 30, 259 male suicide decedents who had IP problems killed their partner. IP homicide‐suicide perpetration was positively correlated with suicide by firearm and precipitating civil legal problems but negatively correlated with mental health/substance abuse treatment. An estimated 33.7% of IP homicide‐suicides occurred during a breakup; 21.9% of IP homicide‐suicide perpetrators had domestic violence histories. Conclusions: Connections between the criminal justice and mental health systems as well as stronger enforcement of laws prohibiting firearm possession among domestic violence offenders may prevent IP homicide‐suicides.